Diagnosis dan Tatalaksana Esofagitis Korosif - Tika Hakikah (Jurnal Otorinolaringologi Kepala dan Leher Indonesia, 2023)
Introduction: Corrosive esophagitis is inflammation of the esophagus that occurs due to exposure to acidic or alkaline corrosive substances. Clinical symptoms is not always correlated with the degree of esophagus injury. The degree based on esophagoscopy findings is important in determining management and prognosis as an accurate predictor of complications to death. Objective: To know the diagnosis and management of corrosive esophagitis. Objective: To know the diagnosis and management of corrosive esophagitis. Literature Review: Corrosive esophagitis is most common in children caused by accidental ingestion, and in adults caused by suicide. Exposure to corrosive substances can be acids (sulfuric acid, hydrochloric acid), bases (potassium hydroxide, sodium hydroxide) and other substances. Esophagoscopy is an important examination to assess the degree of esophageal injury suspected of ingesting corrosive substances. Initial management according to the degree of esophageal injury can be in the form of observation, medical and surgical. Conclusion: Corrosive esophagitis occurs due to ingestion of corrosive substances that cause burns in the esophagus. Esophagoscopy is one of the useful diagnostics for assessing the degree of injury to the esophagus with the best time being carried out in the first 12-48 hours after ingestion of corrosive substances. The initial management of ingested corrosive substances is supportive care, observation and administration of medication or surgery according to the degree of injury to the esophagus.